"Bad hombres" at the Southern US border? White nationalism and the perceived dangerousness of immigrants. Issue 3 (September 2021) - Kulig, Teresa C; Graham, Amanda; Cullen, Francis T; Piquero, Alex R; Haner, Murat
As a candidate and as president, Donald Trump heightened the salience of immigration, portraying those crossing the nation's Southern border as "bad hombres" and advocating building a wall blocking their access to the United States from Mexico. Based on a 2019 MTurk study of 465 White adults, the current study found that a clear majority of respondents rejected this stereotype of Southern immigrants as "bad hombres, " judging them to be just as law-abiding as Americans. Importantly, however, the analysis revealed that two innovative measures—Hispanic resentment and, in particular, White nationalism—were consistently related to perceptions of immigrants as criminogenic. Given the growing demographic diversity of the United States, future research should consider the increasing influence of racial/ethnic resentment and White group identity on public opinions about immigration and other justice issues.